Reimplementing Software Interfaces Is Fair Use: A multifactored rationale for denying Oracle's claim against Google. - Samuelson, Pamela (Communications of the ACM, 2021)
The article discusses the U.S. Supreme Court's decision in the case Google Inc. v. Oracle America, Inc. concerning fair use, software interfaces, and reimplementations.